2021
DOI: 10.1002/ente.202100940
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous C,N Codoping Cobalt Phosphates Simply Fabricated via a Mild Host–Guest Strategy as Bifunctional Electrocatalysts for Zinc–Air Batteries

Abstract: It is crucial to develop efficient bifunctional electrocatalysts toward oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) for practical application. Herein, for the first time, Co‐based phosphate ((H2en)0.5CoPO4)) as a precursor with unique CoO4 tetrahedra and diprotonated ethanediamine template (H2en) is simply and rapidly prepared, and the amorphous cobalt phosphate can be obtained via a mild calcination of this host–guest material. Furthermore, the optimal calcined electrocatalyst exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 66 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…It is suggested that MWNT/PBI/NiFeS-xh has crystal/amorphous hybrid structures, and the amorphous structures would play an important role in their high ORR activities. The importance of amorphous structures in the catalysts for the ORR, OER, HER, and water splitting performances has already been reported in many journals. …”
Section: Resultsmentioning
confidence: 97%
“…It is suggested that MWNT/PBI/NiFeS-xh has crystal/amorphous hybrid structures, and the amorphous structures would play an important role in their high ORR activities. The importance of amorphous structures in the catalysts for the ORR, OER, HER, and water splitting performances has already been reported in many journals. …”
Section: Resultsmentioning
confidence: 97%